PENGARUH WORK LIFE BALANCE DAN KOMPENSASI TERHADAP KINERJA KARYAWAN CLEANING SERVICE STUDI KASUS PADA PT. ANGKASA PURA SOLUSI - Agil Deananda Fitri Ayuni; Hamid Halin; Shafiera Lazuarni (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
Human resources are needed in every line of work, so that employees can achieve the goals set by the company optimally, so an employee needs a balance between work and personal life or commonly called work-life balance. This study aims to determine whether there is an influence between the independent variables, namely work-life balance and compensation on the dependent variable, namely performance, both partially and simultaneously. This research was conducted on employees at PT Angkasa Pura I Sultan Mahmud Badarudin II Airport Palembang South Sumatra using descriptive quantitative research methods. The sample in this study was 70 people who took all of the total population. Data collection in this study used a questionnaire and the data was processed using IBM SPSS 23. The results of hypothesis testing found that work-life balance has a positive and significant effect on performance partially with a significance level of 0.000 <0.005 and a t value of 11.363. Partially, compensation is also found to have a positive and significant effect on performance with a significance level of 0.000 <0.005 and a t value of 17.570. Simultaneously, work-life balance and compensation variables both have a positive and significant influence on employee performance variables with an R2 value of 84.8%.